Analisis SWOT Program Banten dan Ulam Pengabenan Perspektif Pendidikan Hindu - Muliani, Ni Made (Jurnal Penelitian Agama Hindu, 2025)
The COVID-19 pandemic has driven a shift in the implementation of Balinese Hindu cremation ceremonies (ngaben) from traditional domestic practices to crematorium-based services. This transition has weakened the transmission of Hindu religious education values, particularly those conveyed through the making of Banten (offerings) and Ulam (ritual foods). This study aims to analyze the strengths, weaknesses, opportunities, and threats (SWOT) of the Banten and Ulam preparation program at Balai Banjar Busana, Sibanggede Village, as an innovative effort to preserve ritual practices and support bereaved families. Employing a qualitative case study approach, data were collected through participatory observation, in-depth interviews with local customary leaders, an online questionnaire involving 32 community members, as well as visual documentation and literature review. The analysis reveals that the program's strengths lie in its efficiency and community-based ritual education; its weaknesses include limited resources and learning media; its opportunities encompass cultural economic potential and curricular integration; while its threats involve ritual commercialization and weakening customary authority. This study offers practical contributions through strategies such as digital module development, flexible scheduling, and reinforcement of spiritual values, which can serve as a replicable model for other Hindu communities in preserving cultural traditions and religious education.